Tanggung Jawab Pidana Petugas Pemasyarakatan Yang Lalai Dalam Melaksanakan Tugas Di Lembaga Pemsyarakatan - Yasmiadi; Iswanto Simanjuntak; Agung Suhendra; Zulpikri (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The state's efforts to meet the basic needs and civil rights of every citizen regarding goods, services, and administrative services provided by public service organizers are known as public service provision. One of the clearest benchmarks for government performance is public service. The public can directly assess the government's performance based on the quality of public services received, as the quality of public services is felt by people from all walks of life. If the performance of public services is built professionally, effectively, efficiently, and accountably, the government's image will improve. Normative legal research supported by empirical research is the type of research used. The role of correctional institutions towards inmates or prisoners in correctional facilities includes several roles, namely: normative roles and the implementation of ideal roles. Criminal Responsibility of Correctional Officers Who Neglect Their Duties in Correctional Institutions. To the authorities, there should be severe sanctions for correctional officers who allow inmates to escape, aimed at providing a deterrent effect. To the Correctional Institution as the party providing public services to the community, it is expected to deliver maximum service, adhering to the established work procedures.